Strategic planning of resources people in the administrative position - For administration employees in state institutions in Iraq - (Journal of the College of Basic Education, 2022)
Planning is an essential component of the administrative process and human resources is the partThe most important in the administrative organization environment that needs planning at both the near and far levelsand development in line with future developments. Human resources are of great importanceAt the present time, it is the management of the most important element in the planning process, which is (human beings).The productive element, the thinker, and the contributor to the productive process, and entering the concept of resource planningHuman as well as the concept of strategic planning into implementation which is based on the foundationsScientific that corresponds between human capabilities and his ability to make appropriate decisions.